2018
DOI: 10.18240/ijo.2018.04.23
|View full text |Cite
|
Sign up to set email alerts
|

Childhood glaucoma profile in Dakahelia, Egypt: a retrospective study

Abstract: PCG is the most prevalent type of childhood glaucoma, followed by acquired glaucoma especially traumatic hyphema. Combined trabeculotomy-trabeculectomy and Ahmed valve implantation are the most common surgical interventions. CGRN classification is found to provide a consensus skeleton and is recommended to be integrated in our routine ongoing clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
9
14
3
Order By: Relevance
“…The male predominance was also noted in populations with high consanguineous births such as in India even in Asian populations in the United Kingdom. 7,9,10 Other single-center studies in the United States also reported a male predominance in childhood glaucoma (Table 5). 12,13 The distribution of JOAG (5.2%) is similar to other reports, having a presentation of <20% in their respective patient populations (Table 5).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The male predominance was also noted in populations with high consanguineous births such as in India even in Asian populations in the United Kingdom. 7,9,10 Other single-center studies in the United States also reported a male predominance in childhood glaucoma (Table 5). 12,13 The distribution of JOAG (5.2%) is similar to other reports, having a presentation of <20% in their respective patient populations (Table 5).…”
Section: Discussionmentioning
confidence: 85%
“…The CGRN Classification system was a tool already used in different regions to describe glaucoma. 9,12 Applying the CGRN system in our patient population provides a way to compare the incidence of childhood glaucoma in other regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations